منهج الإمام البخارى فى الرواية عن الرواة الموصوفين بالتشيع فى كتابة الصحيح مع دراسة نقدية تطبيقية على الرواة المختلف فى درجة تشيعهم - الزامل، وفاء بنت عبدالعزيز بن حمد (الجامعة الإسلامية بغزة - عمادة البحث العلمي والدراسات العليا, 2020)
يعالج هذا البحث مسألة من أدق مسائل علوم الحديث وأهمها، وهي مسألة تناولت رجال البخاري الذين وصفوا بالتشيع، سواء أكان ذلك التشيع ثابتا أم غير ثابت، وكشفت عن منهج البخاري في الرواية عن هؤلاء الرجال، وعددهم ثلاثون رجلا، ثلاثة منهم ترجح لدينا سلامتهم مما وصفوا به من التشيع، فبقي سبعة وعشرون رجلا، اثنان وعشرون منهم تشيعهم يسير، لا يعدو أن يكون ميلا لعلي، وهذا لا يؤثر في عدالتهم، وخمسة وصفوا بالتشيع، واختلف في درجة تشيعهم منهم من وصفهم بالتشيع دون غلو، ومنهم من وصفهم بالغلو، وواحد منهم فقط وصف بالرفض، واستخلصت الباحثة من خلال هذا البحث دقة الإمام البخاري، وبراعته في تأليف صحيحه، واتساق منهجه، واطراد مسلكه، وحسن انتقائه لأحاديث الرواة، وحرص البخاري- رحمه الله- على حفظ سنة رسول الله، وذلك بالأخذ بأحاديث الرواة إذا استجمعت شروط القبول، بغض النظر عن مخالفتهم المذهبية؛ لأن الأمر لا يقتصر- فقط- على صفات الراوي، وإنما يشمل كذلك صفات المروي، وأن الرمي بالتشيع مطلقا ليس بقادح ما لم يبين، وكذلك الغلو ما لم يؤد إلى محرم، فيكون الرد بسبب ذلك المحرم، لا بسبب التشيع.
addresses one of the most sensitive issues of Al-Hadeeth sciences, that is the faith of Shiah, fixed or non-fixed, among Imam al- Bukhari’s followers. The researcher explored Imam al- Bukhari’s approach in narrating conducted among those followers. The follower’s number is thirty men, three of which are suggested to be free of Al Tashayoh accusation. The other twenty-seven men, twenty-two of which are slightly described of Al-Tashayoh. More precisely their Tashayoh is only an inclement towards Ali. The thing that does not affect their moderate status. The other five men were described of Al-Tashayoh and differed in the degree of disobedience to them. Only one of those men were denied of Al-Tashayoh . The researcher concluded to the accuracy and ingenuity of Imam al-Bukhari: in the authorship of the correct, and the consistency of his method, steadiness of course, and his accurate selection of narrators' narrations. Moreover, Al Bukhari is keen to keep Sunna of the Messenger of Allah Mohamad peace be upon him, because it is not only limited to narrator's qualities, but also It is to their qualities. Shiism is characterized unless Bakadh is shown. Nevertheless, hyperbole unless it led to Muharram, so the response is due forbidden not because of Shiism.
Keywords: علم الحديث -- رواة الحديث -- البخارى، أبو عبد الله محمد بن إسماعيل، ت. 870 م. -- الرواة الموصوفين